PENGARUH KEPEMIMPINAN DAN LINGKUNGAN SOSIAL TERHADAP KINERJA KARYAWAN HOTEL MURIA SEMARANG - Aditya Nanda Wihardi; Ari Pradhanawati; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2014)
Leadership an employer who responded positively by employees of Hotel Muria Semarang, will be able to grow the assessment that the employer felt able to lead because they have the skills and be able to establish a good relationship with the employees. The working environment is also an impact on employee performance. Environment conducive working atmosphere and full cooperation to further bolster the performance of employees. Phenomenon encountered by researchers baseline data collection, showed there is still a lack of performance forms shown Muria Semarang Hotel employee.The purpose of this study was to determine the effect of leadership and work environment on performance. The hypothesis of this study is there is influence of leadership and work environment on performance. The population in this study were employees of Hotel Muria Semarang totaling 50 people. This study is a population study. The data in this study were collected by three questionnaires, namely questionnaire performance, leadership, and work environment.The result showed that Y = 8,516 + 0,219X1 + 0,185X2 there is influence of leadership and work environment on employee performance Muria Semarang Hotel.The conclusion of this study is there is influence of leadership and work environment on employee performance Muria Semarang Hotel. Suggestions that can diberkan generally is the Muria Semarang Hotel is expected to remain employees can promote a sense of comfort in working through the supervisor's leadership to understand any difficulties experienced employees in the work, so that the employee can show that the maximum performance.